Effect of transcutaneous stimulation of posterior tibial nerve on overactive bladder : a randomized Controlled trial - SMITA SHINDE; MANISHA RATHI (International Journal of Pharma and Bio Sciences, 2017)
Urinary incontinence (UI) is the involuntary leakage of urine. It is Common health problems among women of old ages with prevalence ranging from 10% to34% in India. UI affects the women physically and psychosocially and worsen their quality of life. Overactive bladder is defined as urgency, with or without incontinence, usually with increased frequency and nocturia. To investigate the effects of Transcutaneous Nerve Stimulation (TENS) of Tibial Nerve on frequency, quality of life, and urgency in women with overactive bladder.In this Randomized Controlled trial, 30 women having overactive bladder problem with age between 35-70 years were selected. Women with pelvic surgery, any neurological problem, pregnancy were excluded. Subjects were divided into 2 groups randomly: Group A (experimental n=15) and Group B (control n=15). Outcome measures were frequency and volume of urination, Visual Analogue Scale for urgency of micturation and King’s health questionnaire for quality of life. Conventional TENS was given on posterior tibial nerve for unilateral leg trice a week for 4 weeks and re-assessment was done at the end of 4th weeks. Statistically significant difference in pre-post frequency of micturation was noted as Gr. A had mean frequency of 2.10 and gr. B had 1.06. Volume of Urine showed significant reduced in Group A (24.29 ml) than group B (9.39 ml). Statistically significant improvements was seen in group A in urgency of micturation and quality of life than group B after 4 weeks of treatment. This study concluded that TENS improves the overactive bladder problems and thus improves the quality of life. TENS on Tibial nerve is cost effective and non invasive technique which can be easily utilized by many women for their treatment without feeling embarrassed.